Perception of sellers and buyers about the presence of stray dogs and cats in the markets and their control strategies in Los Olivos district, Lima-Peru - Sandoval Huamani, Annghie (2021)
The aim of this study was to evaluate the perception of sellers and buyers about the presence of stray dogs and cats within the markets and their control strategy in the Los Olivos district in 2019. In total, 20 sellers and 20 buyers were surveyed in each of the 10 selected markets (total 400 surveys). The results showed that 79.5 and 60.3% of the surveyed observed stray dogs and cats, respectively; 59.2% stated that they had owners; 59.9% of sellers and 36.2% of buyers indicated the presence of dogs in the markets was mainly due to the owners bringing them. Besides, 78.4% said that they represent a problem because they pollute the environment (66.9%), transmit diseases (35.6%) and contaminate food (30.1%). The ailments perceived in stray animals were "malnutrition" (31.3%), parasitosis (24.3%) and accidents (11%). According to them, the responsibility of dealing with the presence of these animals in the market rests in the municipality (37.7%), buyers (32.2%) and the market administration (20.9%). The solution to this problem would be, in the opinion of those surveyed, adoption (43.3%), spaying/neutering (21.2%), awareness of responsible pet ownership (13.2%) and only the sterilization of females (8.6%). The results show the need to implement an awareness programme and compliance with regulations that prohibit the presence of stray dogs and cats in Los Olivos markets.